Intercultural learning in the training process of Venezuelan migrants (Orkopata. Revista de Lingüística, Literatura y Arte, 2022)
Intercultural learning that takes place with migrants in border areas should be understood as a resource and not as an obstacle in schools. In recent years, the flow of migrants has increased, especially from Venezuela, who have the right to education. Therefore, the objective of the investigation was to analyze how intercultural learning contributes to the training process of Venezuelan migrant students of the Tomas Arturo Sánchez Educational Institution, residents of the Municipality of Ipiales - Nariño. The research was developed with a qualitative approach, with a research-action design, using the interview and participant observation. Three types of intercultural learning were defined, managed by the teachers of the Tomas Arturo Sánchez Educational Institution in the municipality of Ipiales, with Venezuelan migrant students, which are: Learning in everyday work situations, learning in migration processes, and learning and research with proposals or contributions. didactic. It was established that learning in migration processes and learning and research with proposals or didactic contributions, present greater frequency in their use, as greater acceptance by students, with high mastery of the teacher and high coverage with reference to the total of migrants enrolled in the institution. Finally, new intercultural learning is proposed to help contribute to the training process of Venezuelan migrant students.
Keywords: teacher; education; cultural exchange; migration